End-of-life hospital care practices: integrative review (Research, Society and Development, 2021)
Decisions about end-of-life care involve several aspects, representing challenges and mobilizing doctors and nurses, professionals who excel in decision-making. This integrative literature review aimed to identify care practices of doctors and nurses at the end of their lives in the hospital. Data collection took place between January and February 2020 in the Web of Science, Scopus and Medical Literature and Retrivial System Online (MEDLINE) databases. 58 articles were selected with the following themes: palliative sedation, order of no cardiopulmonary resuscitation, communication and decision-making, euthanasia and assisted suicide, withdrawal or limitation of life-sustaining treatments, cancer treatments and terminal care. It is concluded that end-of-life care practices focus on physical symptoms and are intended to relieve suffering. Suspending or limiting cardiopulmonary resuscitation, hydration, nutrition and hemodialysis, as well as performing euthanasia or assisted suicide are more controversial.